Placenta Accreta following Hysteroscopic Lysis of Adhesions Caused by Asherman’s Syndrome: A Case Report and Literature Review - Yuko Sonan; Shigeru Aoki; Kimiko Enomoto; Kazuo Seki; Etsuko Miyagi (Case Reports in Obstetrics and Gynecology)
Asherman’s syndrome is defined as partial or complete obstruction of the uterine cavity primarily caused by intrauterine procedures and infections. Hysteroscopic adhesiolysis is commonly used to treat Asherman’s syndrome. Although the frequency of placenta accreta is known to increase with pregnancy after hysteroscopic adhesiolysis, precise data remain unknown. We report a case of placenta accreta following hysteroscopic lysis of adhesions caused by Asherman’s syndrome and IVF treatment and review the literature on placenta accreta following hysteroscopic adhesiolysis. It is necessary to consider placenta accreta as a complication of pregnancies after hysteroscopic adhesiolysis for Asherman’s syndrome, particularly in those conceived using IVF.